A evolução sócioespacial do Bairro Asa Branca dentro do desenvolvimento regional e urbano, a partir dos anos 1980, em Boa Vista- RR - Conceição, Cleudimar Araújo (2017)
The creation, growth and evolution of Asa Branca neighborhood in the city of Boa Vista/RR it is directly associated with the dynamics of production and reproduction of the effort with the direct actior and intervention of actors and the social agents in the state of Roraima. Implyingrow a rapid and disorderly growth of the capital of Boa Vista. Therefore, the work aims to analyze, in the understanding of the authores and sourse. The descussion abouth the urban and regional historio graphe. The socioespatial evolution, Asa Branca neighborhood from the 1990 onwards the disruption of public politics, implanted by the public power with the intention of promoting as an important and strategic comercial center of the capital of Boa Vista. For so much the work was divided in three moments: in the first moment the theoritical approach deals with the genesis of the urban in the Amazon, the formation of the first Amazonian cities, of the (Rio Branco) white river and the efforts to order the territory and the city. The second moment, reflection an the cause ande consequences of the expansion of the urban fabric of Boa Vista, the role of the agents of social actors, this part being essential, for the socioeconomic growth and development of Asa Branca neighborhood then next the work exposes the socio-enviranmental problems present in the neighborhood. The harmony between public policies and the real needs of the residents an for this: we use interview with the actores and space promoting agents, making it possible to aggregate knauledge through reports of experiences . of living the same. This enabledus to broaden the debate about growth of the city Boa Vista and its neighborhoods. The process that led Asa Branca neigborhood to become potencial in the west of the capital , as well as the effectiveness of policies for the neighborhood.